2020
DOI: 10.33087/aksara.v3i2.136
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kalimat Imperatif Pada Tuturan Masyarakat Desa Teluk Raya Kecamatan Kumpeh Kabupaten Muaro Jambi (Kajian Pragmatik)

Abstract: The purpose of this research is to describe the form imperative sentences in the oral speech of the Teluk Raya village society, Kumpeh Regency Muaro Jambi (A Pragmatic study). This research is descriptive qualitative. The primary data is taken from the Imperative sentences (order) of Malay Jambi Kumpeh language on the community of Teluk Raya Village Kumpeh Muaro Jambi district, while the secondary data is derived from books. In collecting the data, uninvolved conversation observation technique, note-taking tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Pragmatik merupakan cabang ilmu bahasa yang mengkaji mengenai penggunaan Bahasa, yang berfokus untuk mengkajimaksud tuturan yang disampaikan oleh penutur dan ditafsirkan oleh mitra tutur (Ningsih & Muristyani, 2021). Berdasarkan hal tersebut pragmatik sangat berhubungan dengan analisis mengenai maksud sebuah tuturan yang digunakan pada tuturan itu sendiri (Amral & Ulfah, 2020;Hasibuan et al, 2022;Panggalo, 2022). Pragmatik ini melibatkan penafsirannya tentang apa yang dimaksudkan oleh orang di dalam sebuah konteks khusus dan bagaimana konteks tersebut memiliki pengaruh terhadap apa yang dikatakan (Krissandi & Setiawan, 2018;Utami & Rizal, 2022).…”
Section: Pendahuluanunclassified
“…Pragmatik merupakan cabang ilmu bahasa yang mengkaji mengenai penggunaan Bahasa, yang berfokus untuk mengkajimaksud tuturan yang disampaikan oleh penutur dan ditafsirkan oleh mitra tutur (Ningsih & Muristyani, 2021). Berdasarkan hal tersebut pragmatik sangat berhubungan dengan analisis mengenai maksud sebuah tuturan yang digunakan pada tuturan itu sendiri (Amral & Ulfah, 2020;Hasibuan et al, 2022;Panggalo, 2022). Pragmatik ini melibatkan penafsirannya tentang apa yang dimaksudkan oleh orang di dalam sebuah konteks khusus dan bagaimana konteks tersebut memiliki pengaruh terhadap apa yang dikatakan (Krissandi & Setiawan, 2018;Utami & Rizal, 2022).…”
Section: Pendahuluanunclassified
“…Imperative sentences in Indonesian range from very harsh or rude orders to very subtle and polite pleas (Thamimi & Wiranty, 2019). In conveying imperative sentences, many things must be considered, namely in which imperative sentences are used, in what situations imperative sentences are used, the relationship between speakers and interlocutors when imperative sentences are used, and the response of interlocutors to imperative sentences delivered by speakers (Amral & Ulfah, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Much previous research about tindak tutur (speech act) and imperative have found the request marker tolong as a politeness marker (Amral & Ulfah, 2020;Rahmawati, 2020;Septiani, Sumarti, & Rusminto, 2018;Wahyuni, Darwis, & Said, 2020). However, novels and movies are edited, so the structure, wording, and others may differ from the natural daily conversation.…”
mentioning
confidence: 99%